THE NARRATIVE TECHNIQUES IN LY LAN’S NOVEL BUU SON KY HUONG - Ngoc Thien Bao, Nguyen; Thanh Tai, Nguyen; Thi Anh Tuyet, Nguyen; Ngoc Bao Tran, Nguyen; Thanh Uyen, Kieu (HNUE Journal of Science: Journal of Social Sciences, 2026)
The article employs a narratological framework in combination with structural and poetics-based approaches to examine the novel’s narrative techniques in Ly Lan’s novel Buu Son Ky Huong. The study shows that the work constructs a multi-layered narrative model through the flexible use of narrative perspective, the combination of linked and interwoven plot structures, and the dialogic organization of tone, which together create a polyphonic narrative discourse. In addition, the novel develops a network of symbols associated with religious and cultural spaces of Southern Vietnam. Based on these analyses, the article clarifies Ly Lan’s narrative techniques in Buu Son Ky Huong and, at the same time, highlights the diversification of narrative strategies in Vietnamese novels in the early decades of the twenty-first century.